Men's educational needs assessment in terms of their participation in prenatal, childbirth, and postnatal care - Saeideh Nasiri; Fatemeh Vaseghi; Seyyed Alireza Moravvaji; Maryam Babaei (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Despite the importance of men's role in prenatal care and its impact on the outcome of a high-risk pregnancy, in many countries, including Iran, men are not aware of their real needs. Since the first step in designing any health plan is to identify the needs of the target population and that no program can be effective without considering the actual needs of the target group, this study aimed to identify men's educational needs for participation in prenatal, childbirth, and postnatal care. MATERIALS AND METHODS: In this descriptive cross-sectional study, 280 men were selected in Kashan city, Iran, in 2015. The sampling method was cluster sampling. The data collection tool was questionnaire designed based on Mortazavi and Simbar's studies that included demographic characteristics of the subjects (14 questions) and their educational needs in terms of the content of the training program, the training method, trainer, time, place of training, all of which were measured by Likert scale and completed by the interview. Data were analyzed by SPSS software version 16 using descriptive statistics. RESULTS: The findings showed that the mean age of the men participating in the study was 35.15 ± 5.83 years. Most men had high school education (45%). The three most important educational needs of men regarding participation in prenatal and postnatal care were maternal nutrition (87.5%), sexual health (86.8%), and warning signs during pregnancy (81.8%). Men preferred to receive information from a physician (93.2%), before pregnancy (91.8%) in healthcare centers (90%). Family was the most important source of information. CONCLUSION: According to men's suggestions, suitable educational programs must be implemented by physicians in healthcare centers in classes of preparation for labor and childbirth or during prenatal care.